Facile Fabrication of Porous Si Microspheres from Low‐Cost Precursors for High‐Capacity Electrode. Issue 3 (18th December 2019) - Geng, Liyuan; Yang, Dandan; Gao, Shilun; Zhang, Zhaoxiang; Sun, Feiyuan; Pan, Yiyang; Li, Shaoqi; Li, Xiaohua; Cao, Peng‐Fei; Yang, Huabin
Abstract: Comparing with nanometer‐sized Si (nano‐Si), the micrometer‐sized Si (micro‐Si) is more promising for the practical applications due to its low cost and scalable production method. Fabrication of micro‐Si with porous architecture can efficiently alleviate the high mechanical stress and severe mechanical fracture. Till now, it is still a challenge to achieve porous micro‐Si with controlled morphology, such as microsphere, from a cost‐efficient and environmentally friendly approach. Herein, a facile approach on fabricating Si microsphere with porous architecture via a low‐temperature aluminothermic reduction (LTAR) method using the low‐cost fumed silica (FS) as raw material is introduced. After compositing with graphite and then coating with amorphous carbon, the SiFS /graphite@carbon (SiFS /G@C) electrode displays superior reversible capacity (730 mAh g −1 after 100 cycles) and excellent rate capability (729.1 mAh g −1 at 1 A g −1 ). The electrochemical performance is much better than that of Si‐microparticles/G@C (Mic‐Si/G@C, 368 mAh g −1 at 100 mA g −1 after 100 cycles). These results show the great potential of SiFS /G@C electrode as an alternative high‐performance electrode material for lithium ion batteries. Moreover, the LTAR adopted in the current study significantly reduces the energy consumption for preparation of Si microspheres from low‐cost raw materials. Abstract : Porous Si microsphere is fabricated via a low‐temperature aluminothermic reduction from the low‐cost fumed silica. After compositing with graphite and coating with amorphous carbon, the electrochemical performance is better than that of Si microparticle based composite electrode. The results show the great potential of porous Si microsphere based electrode as an alternative high‐performance electrode material for lithium ion batteries.